Method Development for Determination and Quantification of Ethanol in alcohol- free beer – Comparison of Size Exclusion Chromatography (SEC), enzymatic- and GC methods - Möller-Hergt, Gustavo; Schorn, Rolf; Schadewald, Gerd; Waterkamp, Hermann-J. (BrewingScience, 2005)
The quantification of ethanol in alcohol free beer is a crucial parameter of the quality assurance in the brewery. Most laboratories use an enzymatic assay whereby ethanol is oxidized and the reduced co-factor is measured by UV spectroscopy. Here we present an alternative method which is readily automated utilizing an HPLC method with size exclusion or gel permeation chromatographic (SEC) stationary phases.This SEC- method provides a new convenient and reliable technique to analyze ethanol in alcohol-free beer. In addition to the enzymatic and GC method the SEC- method allows the determination of ethanol in a wide concentration range with high linearity. Moreover, sugars can be analyzed in the same sample run, whereby hints for the beer production process are provided.